TINGKAT KOMPETENSI SUMBER DAYA MANUSIA DALAM MEMPENGARUHI KINERJA KARYAWAN PT. FAJAR MAKASAR TELEVISI - Guntur Suryo Putro; Arfiany Sahban (UNIVERSITAS MUHAMMADIYAH MAKASSAR, 2020)
The population in this study were all employees of PT. Dawn Makasar Television. While the samples used in this study were 58 respondents, and to test the hypothesis, researchers used descriptive analysis methods and simple regression analysis. Descriptive analysis is used to view and explain respondents' responses and improve employee performance. Indicators used for competency variables include work spirit, development, education level, work productivity, achievements and awards And the indicators used for performance variables are the quality of work, quantity of work, and timeliness of PT employees. Dawn Makasar Television. The results of this study showed that there is an influence between human resource competency variables on performance variables where conducted t test with t calculated test results = 13.11 and t table 1.672 for a significant level of 0.05 means t calculate t table with dk = 58 - 2 = 56. This means the hypothesis in this study which states that there is an influence of human resource competence on the performance of PT employees. Dawn Makasar Television. Keywords: Human Resource Competencies and Performance